Ultrafast reorganization of the hole charge created upon outer-valence ionization of porphyrins - Kuleff, Alexander I.; Lünnemann, Siegfried; Cederbaum, Lorenz S. (Chemical physics, 2012)
Based on elaborated ab initio calculations we first study the ionization spectra of the free-base porphyrin (H2-P) and Mg(II) porphyrin (Mg-P). Then we investigate the ultrafast electron dynamics following outer-valence ionization of these systems which constitutes the highlight of this paper. It is shown that the electron correlation effects are very strong in these systems giving rise to pronounced shake-down satellites in the outer-valence part of the ionization spectra. We show that due to these strong correlation effects the removal of an electron from the 3b1g orbital of H2-P and Mg-P leads to an ultrafast reorganization of the electronic cloud. After being initially localized on the B and D pyrrole rings, the hole charge created upon ionization spreads throughout the molecule in only few femtoseconds. In both systems the electron dynamics triggered by the ionization represent alternating ultrafast delocalizations and localizations of the charge. The results may also give a hint on the nuclear dynamics in the free-base and Mg(II) porphyrin radical cations that will follow the ultrafast charge migration.